Students bullying teachers: Understanding and behavior of college students from a higher education institution - John Mark R. Asio (Journal of Pedagogical Research, 2019)
Student bullying a teacher is a phenomenon given with the least attention and focus since the perpetrators were seen as the academe itself. This descriptive study aims to determine the understanding and behavior of students in a higher education institution towards teacher bullying. The study surveyed 105 conveniently selected respondents from the three (3) different departments of a local community college in Olongapo City who were currently enrolled within the school year of 2017-2018. A draft questionnaire was created and submitted for validity, reliability, and consistency checks from different experts. The data collected were then processed using SPSS 22. The following results were generated: the respondent was a female, 18-20 years of age, first-year level and studying under the College of Business and Accountancy.  The respondents moderately understood the idea of teacher bullying by students and their behavior towards teacher bullying by students is slightly inappropriate. Significant findings were found when the variables were grouped according to the year level and the department. There was also a low direct relationship that was observed between the understanding, year level and department. Based on the results, pertinent institutional policies and programs were recommended and suggested.